2022
DOI: 10.1371/journal.pone.0274588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grain yield stability of tritipyrum as a novel cereal in comparison with triticale lines and bread wheat varieties through univariate and multivariate parametric methods

Abstract: Salinity is a major abiotic stress affecting cereal production. Thus, tritipyrum (x. Tritipyrum), a potential novel salt-tolerant cereal, was introduced as an appropriate alternative for cereal production. The purposes of this study were to evaluate agronomic traits, yield, and yield stability of eight primary tritipyrum lines, five promising triticale lines, and four bread wheat varieties and to screen a stable yielding line. The experiments were conducted in randomized complete block designs with three repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…While the genotypic effects were insignificant at SEA and MCH, the TST results clearly illustrated how different genotypes can exhibit varied performances under different environmental conditions. These insights correlate with previous research in this field, as reported by Eltaher et al [ 27 ], Farokhzadeh et al [ 28 ], and Sukumaran et al [ 29 ], highlighting the critical impact of environmental factors on crop yield and performance. This variability underscores the need for tailored breeding and cultivation strategies considering genetic makeup and location-specific environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…While the genotypic effects were insignificant at SEA and MCH, the TST results clearly illustrated how different genotypes can exhibit varied performances under different environmental conditions. These insights correlate with previous research in this field, as reported by Eltaher et al [ 27 ], Farokhzadeh et al [ 28 ], and Sukumaran et al [ 29 ], highlighting the critical impact of environmental factors on crop yield and performance. This variability underscores the need for tailored breeding and cultivation strategies considering genetic makeup and location-specific environmental conditions.…”
Section: Discussionsupporting
confidence: 91%
“…In this sense, the traits that have been studied to increase seed yield in common bean are pods per plant, seeds per plant, seed weight, and pod harvest index [ 65 ]. However, 100-seed weight is the most important component in determining the yield [ 66 ] because it is less affected by environmental factors than the other yield components [ 67 ]. This is consistent with our results since the trait with the highest number of QTLs was 100-seed weight (100SW) followed by pod harvest index (PHI), which have a positive correlation with the following traits: pods per plant and seed per pod [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The successful exploitation of these resources necessitates a comprehensive understanding of the extent and nature of genetic diversity present within their primary lines. Genetic variation the cornerstone of any breeding effort that offers the potential to introduce valuable attributes such as disease resistance, abiotic stress tolerance, and improved nutritional profiles (Ayalew et al 2018;Sirakov et al 2021;Chernook et al 2022;Farokhzadeh et al 2022a). Moreover, harnessing the diversity present within primary tritipyrum and triticale lines can expedite the development of superior cultivars with tailored characteristics to meet evolving agricultural and consumer demands.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Iranian primary tritipyrum lines, as a new hexaploid (6x) cereal, has been produced from crosses between durum wheat (Triticum durum, 2n= 4x=28, AABB) as the female parent and a brackish sand couch grass specie (Thinopyrum bessarabicum, 2n=2x=14, E b E b ) as the male parent since 1997. Although the early generations of this non-Iranian primary tritipyrum were similar in its morphology, considerable fertility, grain set, and salinity tolerance (250 mM NaCl), but showed a few undesirable agronomic and cytogenetic characteristics, including brittle rachis, late maturity, and low meiotic instability (King et al 1997;Shahsavand Hassani et al 2000;2006;Farokhzadeh et al 2022a). After two decades of cultivation and breeding, efforts to develop a new successful commercial salttolerant crop are inevitable (Pirsalami et al 2021).…”
Section: Introductionmentioning
confidence: 99%